A new tumor-treating device OM-100 with low-frequency magnetic fields inhibits proliferation and metastasis in liver cancer - Xin Zhang; Zhaoxian Yan; Lifa Huang; Xinyan Yu; Rui Huang (BMC Cancer)
Abstract Background This study aims to investigate a novel instrument OM-100 with low-frequency magnetic fields (LFMFs) for its potential applicability in the treatment of liver cancer. Methods Liver cancer cell lines (HepG2 and Huh7) and normal liver cell line THLE-2 were exposed to OM-100 at LFMFs of 0, 10, 25, 50, and 100 kHz for 2 h in the morning, noon, and evening, respectively. The effects of LFMF on cell viability, apoptosis, migration, and invasion capabilities were examined. Additionally, impacts of LFMF on ROS production was assessed. In vivo studies were conducted to examine the safety profile of OM-100 and its effects on tumor growth. Results In vitro, OM-100 reduced the viability of liver cancer cells, increased cell apoptosis, and inhibited cell migration and invasion abilities in a frequency-dependent manner (P < 0.05). In vivo, OM-100 significantly slowed down tumor growth and promoted apoptosis in liver tumors (P < 0.05). Moreover, OM-100 rarely affected the viability of normal liver cells, as well as the health of normal mice. Finally, we further found that OM-100 significantly increased the production of ROS in liver cancer cells (P < 0.05), a key factor in inducing autophagy, which is very important for the progression of liver cancer. Conclusion Our findings reveal the safety of OM-100 and its frequency at 100 kHz significantly inhibits liver cancer progression.